Edukasi Pentingnya Memiliki Growth Mindset pada Peserta Didik di SMA Leppesa 2 Cililin Bandung Barat - Priarti Megawanti (Jurusan Ilmu Pendidikan - Universitas Lampung, 2022)
This community service activity was carried out in order to provide education to students at Leppesa 2 High School about the importance of having a growth mindset. The school, which is located in Cililin, West Bandung, is located on a hill and in the middle of rice fields. To reach the location, we have to go through steep and rocky roads. This school is the only high school in the area. This school was founded because of the desire of the Head of SMA Leppesa 2 so that students who graduated from Junior High School (SMP) could still go to school. So far, many students only go to junior high school because of the distance to Cililin public high school. For this reason, with all his efforts, the Principal of Leppesa 2 High School, eliminated fees for students. It is intended that parents do not feel heavy-hearted to send their children to high school. Despite the risks, the school principal has to sacrifice his salary and certification fees for teacher salaries and additional school infrastructure.